Stakeholder Perception towards the Implementation of National Health Insurance Program - Yuli Susanti; Tita Barriah Siddiq; Siska Nia Irasanti; Rizki Perdana; Yusuf Heriady (Universitas Islam Bandung, 2021)
Indonesian National Health Insurance (NHI) is a social protection program that ensures the fulfillment of basic needs for proper health by implementing a quality and cost control system. There are still differences in perceptions and complaints felt by patients regarding the implementation of the NHI program. The purpose of this study was to evaluate the implementation of the NHI program based on the perception of all stakeholders in the aspect of health equity, quality of service, and health financing. Quantitative research methods with survey techniques on 204 respondents were selected by stratified random sampling in Al-Ihsan Regional General Hospital West Java Province from January to May 2021. The data were analyzed by using the Kruskal-Wallis test and Mann-Whitney U test on the perception of the stakeholder groups. The results showed that the aspects of health equity, service quality, and health financing on the implementation of the NHI program were in a good category. The increase in Healthcare and Social Security Agency (HSSA) insurance premium was considered the lowest aspect. There were significant differences in the perception of stakeholder groups on the aspects of health equity, service quality, and health financing. There were significant differences in perceptions of health equity based on the ages groups and in perceptions of health financing based on income. This indicates that stakeholders' perceptions of the NHI program affected some conditions, including roles in services, ages, and income. PERSEPSI STAKEHOLDER TERHADAP IMPLEMENTASI PROGRAM JAMINAN KESEHATAN NASIONALJaminan Kesehatan Nasional (JKN) merupakan program perlindungan sosial yang menjamin pemenuhan kebutuhan dasar kesehatan yang layak melalui penerapan sistem kendali mutu dan biaya. Masih terdapat perbedaan persepsi dan keluhan yang dirasakan pasien terhadap pelaksanaan program JKN. Tujuan penelitian ini mengevaluasi pelaksanaan program JKN berdasar atas persepsi seluruh stakeholder pada aspek health equity (pemerataan), mutu layanan, dan pembiayaan kesehatan. Metode penelitian kuantitatif dengan teknik survei pada 204 responden yang dipilih secara stratified random sampling di RSUD Al-Ihsan Provinsi Jawa Barat periode Januari−Mei 2021. Analisis data menggunakan Uji Kruskal-Wallis dan Mann-Whitney U terhadap persepsi kelompok stakeholder. Hasil penelitian menunjukkan bahwa aspek health equity, mutu layanan, dan pembiayaan kesehatan pada implementasi program JKN berada dalam kategori baik. Kenaikan premi asuransi BPJS Kesehatan dinilai paling rendah. Terdapat perbedaan signifikan persepsi antara kelompok stakeholder pada aspek health equity, mutu layanan, dan pembiayaan kesehatan. Terdapat perbedaan signifikan persepsi terhadap health equity berdasar atas kelompok usia dan persepsi pada aspek pembiayaan kesehatan berdasar atas pendapatan. Hal ini menunjukkan bahwa persepsi stakeholder terhadap program JKN dipengaruhi beberapa kondisi, antara lain peran dalam layanan, usia, dan pendapatan.